Sovereignty Depends on the Existence of the State in the Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
This essay discusses the inherent relationship between sovereignty and the state and the state's role in realising and implementing sovereignty. Sovereignty, which refers to the highest power in a territory, cannot exist without the state as a legitimate political entity. The state is the foundation of sovereignty, acting as an institution that enforces the law, protects the rights of citizens, and maintains order and security. Through the social contract theory, the state emerges from social agreement to ensure security and justice. The state has the power to make laws, enforce rules, and resolve disputes, which reflects the operationalisation of sovereignty in the life of society. In the international context, sovereignty is recognised as the main attribute of a legitimate state, but it is not absolute because the state must comply with international norms. International recognition of the state is essential for the legitimacy of sovereignty, allowing states to interact at the global level. In conclusion, sovereignty can only exist effectively if a state exercises it, so the state acts as a pillar supporting sovereignty in the legal structure and international system.